Income distribution and government finances in the BOF4 model of the Finnish economy - Juha Tarkka; Alpo Willman (Bank of Finland, 1990)
This paper describes how income distribution and government finances are modelled i n BOF4, a quarterly econometric model of the Bank of Finland. The equations eomprising the ineome distribution and government finanees bloek in the model eonsist of tax equations, behavioural equations for the local government sector and a large number of accounting identities linking produetion and prices to incomes ofhouseholds and other seetors of the economy.
URN:NBN:fi:bof-201807311793
Keywords: 330